A carbon fiber thermoelectric generator integrated as a lamina within an 8-ply laminate epoxy composite: Efficient thermal energy harvesting by advanced structural materials. (1st November 2019) - Karalis, George; Tzounis, Lazaros; Lambrou, Eleftherios; Gergidis, Leonidas N.; Paipetis, Alkiviadis S.
Graphical abstract: Highlights: Thermal energy harvesting by structural composites towards green transport. TEGs consisting of carbon fiber tows used as reinforcements in advanced composites. TEG-enabled structural composites for Energy saving in Aeronautics and Automotive. Achieved power output 0.87 · 10 −6 W at ΔT = 75 K with VTEG 19.56 mV and RTEG ≅ 100 Ω. Abstract: For the first time, the fabrication of a thermoelectric generator (TEG) consisting of carbon fiber (CF) tows and its integration as a lamina within an 8-ply laminate epoxy composite is reported. Commercially available M40B and A-38 CF tows exhibited a Seebeck coefficient ( S ) of +33.85 μV/K (p-type) and −11.83 µV/K (n-type), respectively. Scanning electron microscopy highlighted the CF morphological characteristics and the fiber mean diameters. Electrical conductivity measurements revealed the extremely high values of 1.63 ± 0.04 × 10 5  S/m for the CF-M40B and 1.14 ± 0.03 × 10 5  S/m for the CF-A38. CF-M40B of 33.4 mm length were employed to fabricate a TEG consisting of ten serially interconnected thermocouples. The TEG-enabled CF reinforced polymer (CFRP) composite consisted of unidirectional fabrics at an alternating [0/90]2s symmetric configuration, with the CF TEG module comprising the bottom lamina. The CFRP TEG laminate exhibited a voltage output of 19.56 ± 1.31 mV at a temperature difference (Δ T ) of 75 °C. A reference CFRP was tested in terms of mechanical performance via three point bending and compared to the TEG-enabled one. Finite Elements modeling validated the CFRP thermoelectric performance corroborating the experimental findings. Structural TEG-enabled CFRPs demonstrated for the first time in this work are envisaged to harvest thermal energy losses on a large scale during the operational lifetime of advanced composites.